Reliability and Validity of Turkish Version of Short Form of the Social Role Participation Questionnaire in Patients With Ankylosing Spondylitis - Yesim AKYOL,; Yasemin ULUS,; Yüksel TERZİ,; Ayhan BİLGİCİ,; Ömer KURU, (Archives of Rheumatology, 2018)
Objectives: This study aims to evaluate the reliability and validity of the Turkish version of the Short Form of the Social Role Participation Questionnaire (s-SRPQ) in Turkish patients with ankylosing spondylitis. Patients and methods: The Turkish version of s-SRPQ questionnaire was obtained after a translation and back translation process. The study sample included 100 ankylosing spondylitis patients (59 males, 41 females; mean age 42.0±11.0 years; range 19 to 69 years). To assess the test-retest reliability of the Turkish s-SRPQ, the questionnaire was reapplied 15 days after the first interview (interclass correlation coefficient [ICC]). Cronbach’s alpha (a) was used to evaluate the internal consistency. The s-SRPQ was compared with Short Form-36 (SF-36) survey, Ankylosing Spondylitis Quality of Life questionnaire (ASQoL), Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Bath Ankylosing Spondylitis Functional Index (BASFI), and Satisfaction With Life Scale (SWLS) for convergent validiy. Results: For s-SRPQ/experienced physical difficulties; the individual item ICC ranged from 0.78 to 1.00 and Cronbach’s alpha value ranged from 0.88 to 1.00. For s-SRPQ/satisfaction with role performance; the individual item ICC ranged from 0.93 to 0.98 and Cronbach’s alpha value ranged from 0.96 to 0.99. The Turkish version of s-SRPQ/experienced physical difficulties scores correlated with the SWLS and SF-36 sub-parameters negatively; and Ankylosing Spondylitis Disease Activity Index, and BASFI, and ASQoL positively. The SRPQ/satisfaction with role performance scores correlated with the SWLS and SF-36 sub-parameters positively; and BASDAI, and BASFI, and ASQoL negatively. Conclusion: Turkish version of s-SRPQ has good comprehensibility, internal consistency, and validity and is an adequate and useful instrument for the assessment of participation in Turkish patients with ankylosing spondylitis.